Prevalence of inflammatory back pain and radiologic sacroiliitis is increased in patients with primary Sjogren's syndrome - Eren, Rafet; Can, Meryem; Alibaz Öner, Fatma; Yılmaz Öner, Sibel; Yılmazer, Barış; Çefle, Ayşe; Direşkeneli, Haner; Atagündüz, Pamir (African Field Epidemiology Network-Afenet, 2018)
Introduction: The prevalence of Sjogren's syndrome (SS) in patients with the diagnosis of SpA has been reported to be higher than normal population. Yet, the vice-versa is unclear. In this study, we aimed to investigate the prevalence of IBP, radiologic sacroiliitis and SpA in patients with primary SS. Methods: 85 patients followed at the rheumatology clinics of the Marmara and Kocaeli Universities with the diagnosis of primary SS between November 2011 and August 2012 were included in this study. The control group consisted of 100 age-and gender-matched patients. Inflammatory back pain and axial SpA were diagnosed according to the assessment of spondylo arthritis International Society (ASAS) criteria. Results: 83 patients were (97%) female and 2 (3%) were male. Mean age of the patients was 49.1 (+/- 11) years. Mean disease duration was 7.3 (+/- 4) years. The patient and control groups were comparable in terms of age and gender (p>0.05). Inflammatory back pain was observed in 21 (24.7%) of 85 primary SS patients and in 4 (4%) of 100 control subjects (p<0.001), radiographic sacroiliitis was demonstrated in 9 (10.5%) of primary SS patients and 2 (2%) of the control subjects (p=0.025). Remaining SpA findings were not encountered in either group. Conclusion: inflammatory back pain and radiologic sacroiliitis is increased in patients with primary SS. Whether IBP, SI joint inflammation and radiologic sacroiliitis is due to the co-existence of SpA and primary SS or IBP is an underdiagnosed clinical feature of SS deserves further studies of large patient numbers.
WOS: 000437779600001
PubMed ID: 30344882
Keywords: Inflammatory Back Pain; Axial Spondyloarthritis; Primary Sjogren's Syndrome